Educational Rights from the perspective of inclusive education: a study of the Specialised Educational Service: um estudo sobre o Atendimento Educacional Especializado - Faustino, Carlos Roberto; Orrú, Sílvia Ester (Argumentum, 2021)
The present article aims to assess, from an inclusion perspective, the contribution of the Specialised Educational Attendance (SEA) service in guaranteeing Educational Rights. It was conducted through field research based on the Qualitative Epistemology of González Rey. It concludes that the institution of the SEA does not, by itself, have the power to deliver what is expected of it, however, with the committed application of those involved in the process, it is an essential element for guaranteeing educational rights, from the perspective of inclusive education.